Antikinių dramų pastatymai Lietuvoje - Dikmonienė, Jovita (Literatūra, 2015)
Performances according to antique dramas and their revamps by Lithuanian directors of 1925 to 2003 are presented in the article. Performances of Sophocles’ and Euripides’ tragedies are discussed wider. Scilicet: “Oedipus at Colonus” by Borisas Dauguvietis (1939), “Oedipus the King” by Juozas Miltinis (1977), “Electra” by Irena Kriauzaitė (1993), “Medea” by Linas Marijus Zaikauskas (1994), “Oedipus the King” by Rimas Tuminas (1998), “Antigonė” by Birutė Marcinkevičiūtė (Mar) (1999) and “Oedipus the King” by Oskaras Koršunovas (2002). Scenography and direction of performances, interpretation of antique text and particularity of development of performances’ form and content are analyzed in the article. Scenography of performances changed from realistic (by B. Dauguvietis) and static (by J. Miltinis) portrayal of antique theatre to modern (by L. M. Zaikauskas), plastic (by R. Tuminas) with vivid reflection of today’s realia (by O. Koršunovas). B. Dauguvietis has saved almost authentic form of antique performance and has rejected only from masks and cothurni. Idea of antique marble statuary playing in the tragedy of “Oedipus the King” was rendered in J. Miltinis’ performance. Role of chorus was retained in these performances; original text was not changed or shortened. Plays by I. Kriauzaitė and B. Marcinkevičiūtė were up-to-date, without antique costumes and masks, and distinguished from other plays with its minimalist direction and scenography. Chorus parts, which were acted by one actress, were shortened in “Electra”. Director and actress B. Marcinkevičiūtė herself performed all personages in tragedy and tragedy’s chorus was represented by video projection in “Antigonė”. Later performances of antique dramas were modernized not only in the meaning of form but of content, too. Greek tragedy’s text remained plot’s pattern in L. M. Zaikauskas’ and O. Koršunovas’ performances, through which present-day realia were revealed: women emancipation was revealed in “Medea” and politician’s caricature – in “Oedipus the King”. Antique chorus role was retained in both performances, while masks – in Koršunovas’ performance. Scenography was abstract in “Oedipus the King” by Tuminas, neither representing antiquity nor nowadays. A conclusion is drawn that most Lithuanian directors trended into creation of jug-handled, idealized character (B. Dauguvietis, J. Miltinis, I. Kriauzaitė, B. Marcinkevičiūtė), melodramaticallity (I. Kriauzaitė, L. M. Zaikauskas) or tragicomedy (R. Tuminas). None of directors managed to show universality of antique tragedy so that both past and present would be reflected in it. They, using texts of antique tragedy, created modern picture of distinctive, idealized and psychologized, alone, reserved, depending on destiny human being.